Gleby obszarów zurbanizowanych - nowe podejście na nowe czasy = Soils of the urban areas new approach for the new times - Greinert, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The anthropogenic soils make up the more and more essential part of soil cover of the World. Till present moment the diagnostic, classifying as well as interpretative problems have been noted, which are relating to the soils of urban, industrial, postindustrial and communication areas. The main duties in the face of described problems rest on soil scientists, ecologists of anthropogenic areas, as well as people setting up the norms and legal acts. The urgent necessity of today's time is including Poland to the work in rams of UE thematic strategy for soil protection.
Keywords: gleba - definicja; gleby miejskie; ekologia miast; gleba - prawo; urban soils; urban ecology; soil - definition